The role of oscillatory modes in US business cycles - Andreas Groth; Michael Ghil; Stéphane Hallegatte; Patrice Dumas (Fondazione Eni Enrico Mattei (FEEM), 2012)
We apply the advanced time-and-frequency-domain method of singular spectrum analysis to study business cycle dynamics in a set of nine U.S. macroeconomic indicators. This method provides a robust way to identify and reconstruct shared oscillations, whether intermittent or modulated. We address the problem of spurious cycles generated by the use of detrending filters and present a Monte Carlo test to extract significant oscillations. Finally, we demonstrate that the behavior of the U.S. economy changes significantly between episodes of growth and recession; these variations cannot be generated by random shocks alone, in the absence of endogenous variability.
Keywords: C15; C60; E32; 330; Advanced Spectral Methods; Comovements; Frequency Domain; Monte Carlo testing; Time Domain